An overview of the contemporary Croatian historiography on education (2000-2018) - Krpić, Amir (Historical Thought, 2025)
This paper shows an overview of the achievements of historiography regarding education in the Republic of Croatia in the 21st century. The paper represents an attempt of bringing all results achieved by Croatian historiography regarding the forementioned question. Due to the number of different kinds of publications, only the basic information are represented in the paper, i.e. information about authors, publication year, publishers, journals (for articles), number of pages i bibliography of the publication. Therefore, this paper is not about content analysis of the publications, so it does not pretend to be an analysis of the Croatian historiography achievements regarding the forementioned question in the specified period. The main aim of this paper was to present all publications regarding the question at one place. The author reserves a possibility that some publications, unintentionally, may have been omitted from this overview.